2013
DOI: 10.1002/jsfa.5964
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physicochemical and sensory characteristics in raw and grilled ovine meat

Abstract: This information may be useful for describing and predicting ovine meat quality for both consumers and processors. Therefore, vacuum-packaged ovine meat can be stored for 14 days without disagreeable color to the consumer, and the raw meat texture is tender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
(36 reference statements)
2
5
1
Order By: Relevance
“…Significant differences in instrumental tenderness among different sheep breeds have been reported by other authors . Most of Warner Bratzler shear force values found in this study were comparable to those reported by Ekis et al for five different lamb breeds from the Marmara Region, in Turkey (between 3.66 and 5.05 kg) and by Martínez‐Arellano et al for 1‐year‐old Pelibuey lambs (between 3.3 and 4.1 kg), except for WDB and Santa Inês, which were higher. However, shear force values of lamb meat reported in other studies are, in general, lower than those found in this study.…”
Section: Resultscontrasting
confidence: 99%
“…Significant differences in instrumental tenderness among different sheep breeds have been reported by other authors . Most of Warner Bratzler shear force values found in this study were comparable to those reported by Ekis et al for five different lamb breeds from the Marmara Region, in Turkey (between 3.66 and 5.05 kg) and by Martínez‐Arellano et al for 1‐year‐old Pelibuey lambs (between 3.3 and 4.1 kg), except for WDB and Santa Inês, which were higher. However, shear force values of lamb meat reported in other studies are, in general, lower than those found in this study.…”
Section: Resultscontrasting
confidence: 99%
“…change in lamb longissimus tenderness occurs between days 1 and 7. Ageing beyond 7 days did not significantly improve tenderness, as reported previously (Hope et al, 2013;Koohmaraie et al, 1991;Martínez-Arellano, Severiano-Pérez, Fernández, & Ponce-Alquicira, 2012). Ageing was highly related to PS, desmin degradation and shear force.…”
Section: Proteolysis As An Indicator Of Shear Forcesupporting
confidence: 77%
“…Similar trends were also observed in other muscle food, such as ovine and camel. 34,35 Deterioration of textural properties might be caused by the degradation of the extracellular matrix of beef muscle by microorganisms or the endogenous enzyme system, which could be supported by the microstructural change shown in Fig. 5.…”
Section: Tpa Analysismentioning
confidence: 93%